Are online discussions enough to constitute communities of practice in professional domain? A case study of ergonomics' practice in France. Issue 2 (May 2016) - Barcellini, Flore; Delgoulet, Catherine; Nelson, Julien
Abstract The goal of our research is to characterise how online discussions may provide support to the construction of a Virtual Community of Practice, as a way to develop a profession. To do so, we investigate the functions (sharing information, resources or experience) and the nature of knowledge (e.g. methodology and trends of ergonomics) exchanged on Ergoliste, a French-speaking online mailing list dedicated to ergonomics, as well as the status of participants. Our results reveal that the list has both informative and formative functions as it deals with sharing/seeking information, resources and experience, mainly between experts and novices in ergonomics, exchanging about situated and circumstantiated aspects of practices. Finally, these results are complemented by interviews with list participants which on the one hand confirm the main functions of the list and, on the other hand, reveal divergence in the perception that list participants belonging to a "community" structured only around this list. This research opens some prospects for more longitudinal investigations of the contents of the list, to analyse more deeply how the list can be viewed as an efficient tool to co-elaborate knowledge about ergonomics and its development.